Adherence, belief, and knowledge about oral anticoagulants in patients with bioprosthetic heart valve replacement: a cross-sectional study - Ni, Yun-Xia; Liu, Lu-Lu; Feng, Huang; Li, Zhi; Qin, Chao-Yi; Chen, Miao (Frontiers in Pharmacology, 2023)
Aims: To investigate adherence to oral anticoagulants among patients after mechanical heart valve (BHV) replacement and further examine the mediating role of medication belief in the relationship between knowledge and medication adherence.The number of patients who undergo BHV replacement has increased in recent years. Short-term anticoagulant therapy is recommended for patients after BHV replacement. However, little is known about adherence to oral anticoagulant therapy and the underlying mechanisms among patients with BHV replacement. Methods: A cross-sectional study was conducted between September 2022 and November 2022. A convenience sample of 323 patients who underwent BHV replacement was recruited from a tertiary public hospital in Southwest China. Data were collected by using the 8-item Morisky Medication Adherence Scale, Beliefs about Medicines Questionnaire-specific, and the Knowledge of Anticoagulation Questionnaire. The mediation model was tested by Hayes's PROCESS macro. The STROBE checklist was used.Results: Approximately 17.3% of participants had low adherence, 47.1% had medium adherence, and only 35.6% reported high adherence to oral anticoagulants. Knowledge and necessity beliefs were positively related to medication adherence, while concern beliefs were negatively correlated with medication adherence. Medication belief mediated the relationship between knowledge and adherence to oral anticoagulants. 2 Conclusion: Patients with BHV replacement demonstrated relatively low adherence to oral anticoagulant therapy. Efforts to enhance medication adherence should consider improving patients' knowledge and medication beliefs.